Event prototypes in airline transport operations - Clewley, Richard; Nixon, Jim (Chartered Institute of Ergonomics and Human Factors, 2016)
Evidence from accident reports indicate that pilots are not always able to categorise events in real-time, which can lead to delayed or inappropriate response. The prototype view proposes that category judgements are influenced by the clearest and best cases of category membership. Flight crew may not always experience events and situations in their prototypical forms. We outline future research on event prototypes in airline transport operations in order to develop better explanations of event judgements amongst flight crew.
Keywords: Flight safety; abnormal events; categorization; prototypes